Perbedaan Stress Kerja Pada Karyawan Bank Nagari di Kota Padang Ketika Melaksanakan Work From Home dan Work From Office di Masa Pandemi Covid-19 - Kartmas, Alpinto (Efisiensi: Jurnal Penelitian dan Pengembangan Ilmu Manajemen, 2024)
At the end of 2019, the world was shocked by the emergence of the Covid-19 Virus. Until finally it spread to Indonesia in early 2020. In addition, COVID-19 was designated as an Extraordinary Event (KLB) and took a policy by dividing the work system by the company, namely continuing to work in the office Work From Office (WFO) and working from home or Work From Home (WFH). This study was conducted on 150 subjects who were divided into two groups, where 75 subjects were for the WFH group and 75 subjects for the WFO group. The sampling technique in this study used a purposive sampling technique. Based on the results of the Mann Whitney test, a significance value of 0.006 was obtained, so Ha was accepted and H0 was rejected. This means that there is a difference in the level of work stress between employees who WFH and employees who WFO during the pandemic at Bank Nagari in Padang City.